Validity and reliability of the Arabic version of Muller's prenatal attachment inventory. (3rd July 2021) - Arafah, Dima; Thomas, Bejoy; Fenton, Tanis R.; Sabr, Yasser; Metcalfe, Amy
Abstract: Purpose: Maternal fetal attachment (MFA) is the bond between the mother and her unborn baby. Presently no tools measuring MFA are available in Arabic. The aim of this study was to translate Muller's Prenatal Attachment Inventory (PAI) from English to Arabic, examine the cultural appropriateness of this tool, and test its psychometric properties with pregnant women in an Arab country. Materials and methods: The PAI was translated from English into Arabic using the Universal Translation Approach (modified tool) and assessed for content validity. During this process four additional items were identified for measurement relevance and cultural acceptability resulting in the revised tool. The psychometric properties of the modified and revised tools were assessed after 250 pregnant Arab women completed the PAI. Factor analysis was conducted to assess construct validity, while reliability was assessed using Cronbach's alpha coefficient. Results: Both tools were shown to be unidimensional with excellent reliability (Cronbach's alpha = 0.88 for the modified tool and 0.89 for the revised tool). Nulliparity, planning to breastfeed the baby, feeling fetal movements, and downloading a smartphone app to follow the baby's growth were associated with increased MFA in the PAI, while only planning to breastfeed the baby, feeling fetal movements, and downloading a smartphone app to follow the baby's growth were associated with increased MFA in the revised PAI. Conclusion: The Arabic version of the PAI is a culturally appropriate tool to measure MFA amongst Arabic-speaking women.